Factors Influencing Attitude Making in The Prevention of Anemia in Female Adolescent: A scoping review - Isti Sulistyana Djati; Sri Achadi Nugraheni; Ayun Sriatmi (Publikasi Indonesia, 2025)
Anemia is a significant health issue among adolescent girls, particularly in developing countries. This study aims to explore the relationship between nutritional knowledge and attitudes toward anemia prevention in adolescent girls through a scoping review. The research methods included a literature search from databases such as PubMed, SINTA, and ScienceDirect, with inclusion criteria comprising articles in English or Indonesian published between 2019-2024. Fifteen studies were selected for analysis based on these criteria. The results show that increasing nutritional knowledge, particularly regarding iron intake and balanced diets, can enhance positive attitudes toward anemia prevention. School-based nutrition education programs and innovative media have proven effective, although socioeconomic challenges and access to nutritious food remain obstacles. In conclusion, sustainable nutrition education interventions are essential to reducing the prevalence of anemia among adolescent girls.